Economic stressors and mental health symptoms among Bangladeshi rehabilitation professionals: A cross-sectional study amid COVID-19 pandemic. Issue 4 (April 2021) - Ali, Mohammad; Uddin, Zakir; Hossain, Ahmed
Abstract: Background: Mental health symptoms are considered a public health concern by many professionals and are frequently impacted by factors related to occupation, employment opportunities, and economic stressors. This study investigated the relationship between economic stressors and mental health symptoms among Bangladeshi rehabilitation professionals. Methods: We conducted a cross-sectional survey of 420 rehabilitation professionals between July 2020 and October 2020. Economic stressors were measured using Economic Hardship Questionnaire, Financial Threat Scale, and Financial Well-Being Scale. Mental health symptoms were measured using the Depression, Anxiety, and Stress Scale (DASS-21). Multivariable logistic regression analysis was performed to find associated factors on mental health problems after adjusting confounders. Results: Among 420 rehabilitation professionals 62.1% were male, 38.6% were post-graduated and 75% were in practice. The overall prevalence of depression, anxiety, and stress was 51.0%, 58.6%, and 33.6%, respectively. The multivariable regression analysis indicated that without a high professional degree, lack of opportunity to practice, and loss of income were the associated factors for mental health symptoms. The modelling of the structural equation showed that financial threat is significantly associated with mental health symptoms. Conclusion: During the era of COVID-19, a high prevalence of mental health symptoms was observed among rehabilitation professionals. To minimize the burden of mental health, we recommend that all rehabilitation organizations and the government come together to create equal opportunities to practice and enable individuals to obtain high professional degrees. Abstract : Bangladesh; COVID-19; Depression; Anxiety; Stress; Economic stressors; Financial stress; Rehabilitation professionals.